PEMBELAJARAN BERBASIS RISET DENGAN PENDEKATAN SAINTIFIK DALAM PENINGKATKAN KETRAMPILAN PROSES IPA BAGI SISWA SD - Chrysti, Kartika s (Universitas Sebelas Maret, 2014)
Teaching style of teachers by traditional style is explaining teory, giving example and drill cause acheivement can not be optimal. There for of bad style teaching is not exact in improving capability problems solving, because pupils is not creative and tendency show by teacher example. There for is need effective learning aproach in improving problems solving of pupils specially in natural science learning. The aims of paper is explaining Research Based Learning (RBL) by scientific approach can be effective in improve process sklill science in elementary school.Scientific approarch in learning consist of observation, question, doing, processing, presentation, conclusion, and create can be applied in all learning subject. Keywords: scientific approach, process skill, natural science